C# Console and Windows Forms Development with LINQ and ADO.NET - Williams, Trevoir (Packt Publishing, 2020)
A one-stop resource to learn how to build a practical data-driven Windows Forms application using C#, LINQ, and SQL Server Express About This Video Become familiar with C#, Language Integrated Query (LINQ), ADO.NET, and SQL server concepts Learn how to apply the principles of object-oriented programming in C# Get ready to build and run amazing Windows Forms applications In Detail C#, the most versatile programming language in the .NET framework, allows developers to build Windows, web, and mobile applications. It has strong community support, and more than five million developers prefer C#. This course will teach you how to build a Windows Forms application using C#. The course starts by highlighting the learning objectives and explains the installation process of Visual Studio 2019. Next, you will learn the basic and advanced concepts of C# console programming needed for application development. You will also understand how to use WinForms, ADO.Net, and Language Integrated Query (LINQ) to create WinForms applications. Moving along, you will learn to build data-driven GUI applications using Windows Forms and manage databases with SQL server management studio. Next, you will understand the concept of user management and learn how to use utility classes for keeping the code clean. Later, you will learn to develop multi-document interface (MDI) applications and learn the techniques to add a Visual Studio project to source control. By the end of this course, you will have developed essential skills needed to build data-driven Windows Forms applications using C#, LINQ, and SQL server express.
Online resource; Title from title screen (viewed December 14, 2020)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos